Bureaucracy, the profession, and retention of Captains in the U.S. Army - Williams, Bryan Matthew (Kansas State University, 2019)
This research examines if the U.S. Army has a problem retaining high performing junior officers, with a focus on officers with the rank of Captain. It is theoretically posited that officer retention is influenced by a contradiction that exists between the profession of being an army officer and the social context of the bureaucratic structures in which officers are embedded. Specifically, the formal, rational bureaucratic structures utilized by the army restrict the agency of individual officers in making professional career decisions. In turn, it is hypothesized that this serves as a disincentive for officers to remain in the army. A methodology is developed for categorizing the performance characteristics of U.S. Army Captains. Retention rates are compared among Captains with different performance levels. Logistic regression analysis is used to identify correlates between Captains' perceptions of army bureaucratic structures and their planned career decisions. The results of this study can inform the development of retention strategies or policies that target the retention of high performing Captains in the U.S. Army.
Keywords: Bureaucracy; Retention; Officer; Profession